ANALISA KELAYAKAN PENERAPAN USAHAKBMCLOTH DENGAN METODE LEAN CANVAS - Angger Ridho Safaat (2022)
KBMCLOTH is a business or business that sells jackets. However, as long as the KBMCLOTH business is running, there is a shortage of jacket stock storage space and will rent a place or warehouse for storage. The purpose of this research is to find out whether the KBMCLOTH business is feasible to run from a financial point of view which is calculated using the calculations of the NPV, IRR, PP, and PI values and create a Lean Canvas based on the results of interviews that are used for strategies that must be carried out by KBMCLOTH for business. it can last. The study used 3 conditions, namely Optimistic, Best, and Pessimistic. Based on the results of the research, Optimistic conditions are most appropriate to be applied to the KBMCLOCTH business because the NPV value is Rp. 484.432,202, and the payback period is 4 months and 16 days, the PI value is 21, and the IRR value is 249%.